Contrast enhanced ultrasound in the evaluation and percutaneous treatment of hepatic and renal tumors. Issue 9 (September 2015) - Meloni, Maria Franca; Smolock, Amanda; Cantisani, Vito; Bezzi, Mario; D'Ambrosio, Ferdinando; Proiti, Maria; Lee, Fred; Aiani, Luca; Calliada, Fabrizio; Ferraioli, Giovanna
Highlights: Image-guided percutaneous ablation techniques are increasingly being used for the treatment of malignant tumors of the liver and kidney when surgery is not indicated. Percutaneous ablation relies on imaging at every step of the process in order to detect, guide, and confirm complete tumor coagulation. CEUS is a real-time dynamic imaging technique that plays an important role in the management of patients treated with ablation for malignant tumors. This review focuses on the role of CEUS in the evaluation of patients undergoing percutaneous treatments for hepatic and renal tumors. Abstract: Image-guided percutaneous ablation techniques are increasingly being used for the treatment of malignant tumors of the liver and kidney. Contrast enhanced ultrasound (CEUS) is a real-time dynamic imaging technique that plays an important role in the pre-, intra-, and post-procedural management of these patients. This review will focus on the role of CEUS in the evaluation of patients undergoing treatment with percutaneous ablation for hepatic or renal tumors.